Konseling Kelompok Berbasis Islam Dengan Pendekatan Cognitive Behavior Therapy (Cbt) dalam Meningkatkan Kematangan Karir Siswa - Aini, Jannatun; Ristianti, Dina Hajja; Azwar, Beni (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2024)
Humans cannot be free from problems, whether they realize it or not, children, teenagers, adults and even old people can definitely have problems in their lives. Adolescence is the most formative period, especially in terms of the ability to choose a path to adult life and the possibility of employment at risk of developing as a teenager, accompanied by the need to start preparing for future employment. Group counseling services are a type of service that can help teenagers overcome obstacles that prevent them from achieving career maturity. A review of relevant literature is used as an approach, and is supported by the findings of a number of papers, journals, books and other supporting documents. One approach from group guidance services that can help with career maturity issues is the Cognitive Behavior Therapy (CBT) approach. Cognitive Behavioral Therapy is effective in increasing career maturity.